Characterization of the whole plastome of Dipentodon Sinicus (Dipentodontaceae). Issue 2 (3rd July 2019) - Liu, Changkun; Liu, Lili; Jin, Lei; Yang, Zhenyan; Ji, Yunheng
Abstract: In this study, we sequenced and assembled the whole plastome of Dipentodon sinicus . The plastome was 158, 020 bp in length and consisted of a pair of inverted repeat regions (IRs, 26, 551 bp), a large single-copy region (LSC, 86, 624 bp) and a small single-copy region (SSC, 18, 294 bp). It encoded 114 unique genes (80 protein-coding genes, 30 tRNA genes and 4 rRNA genes). Phylogenetic analysis showed that Dipentodon sinicus was sister to Tapiscia sinensis .